The Effect of Product Quality and Price Perception on Purchase Decisions and Customer Satisfaction as Intervening Variables at Rodalink Jakarta Outlets - Rezal, Yonggi Noval; Muharam, Hari; Pranowo, Agus Setyo (Universitas Pakuan, 2023)
In general, this study aims to find ways and strategies to improve purchasing decisions so that they can be input and recommendations for related parties, namely Rodalink Jakarta and consumers. The method used in this study is a survey method with a correlational approach. Information from the survey results was collected from respondents using a questionnaire for all variables, both the Purchase Decision (Y), Product Quality (X1), Price Perception (X2), and Customer Satisfaction (Z) variables. The population in this study is a member of the Polygon Xtrda Indonesia Community Jakarta totaling 278 people. The sampling technique in this study used a proportional random sampling technique using the Slovin formula with an error margin of 5%, a sample of 165 people. Data processing in this study used descriptive analysis techniques and inferential analysis with a correlational approach. The results obtained that Product Quality has a direct and very significant positive effect on Purchase Decisions through Customer Satisfaction so that strengthening Product Quality through Customer Satisfaction can indirectly improve Purchase Decisions with a beta value of 0.190 while the indirect effect of Product Quality on Purchase Decisions through Customer Satisfaction namely: 0.190 x 0.093 = 0.018 then the total effect given is: 0.190 + 0.018 = 0.208, this shows that Product Quality indirectly significantly influences Purchase Decisions through Customer Satisfaction.